PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI PEMEDIASI PADA KONSUMEN RESTORAN CANAI MAMAK KL DI BANDA ACEH - Dara Adelina, M. Ridha Siregar (Departemen Manajemen, 2019)
Abstact: This study aims to measure the effect of sevice quality to Loyalty with satisvation as mediating variable. The sample used in this restorant canai mamak KL Banda Aceh is totaling 103 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is Purposive Sampling. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect of all the variables involved. Based on the results of the HLM analysis indicated that service quality positively influence Loyalty, service quality positively influence satisvaction, satisvaction positively influence Loyalty and satisvaction mediate the relationship between Service Quality and Loyalty.Keywords: Service quality, Loyalty, Satisvaction , Hierarchical Linear Modelling